Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/dth.13473
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate for the treatment of recalcitrant genital and extragenital lichen sclerosus: A retrospective series

Abstract: Lichen sclerosus (LS) is a chronic, difficult-to-treat, skin disease that predominantly affects the anogenital region and presents with atrophy, hypopigmentation, pruritus, burning, and scarring. 1 Systemic treatments are often utilized in patients with recalcitrant or disseminated disease; however, their use is limited by a paucity of data regarding efficacy and associated adverse effects. 2-8 This study evaluated the efficacy and safety of methotrexate (MTX) for the treatment of recalcitrant genital and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Indeed, a recent series has examined the efficacy of methotrexate in forms resistant to topical treatment. [ 11 ] In our series, the improvement under DC of localized forms is partial, which implies that acitretin seems to be efficient in diffuse forms. On the other hand, chloroquine, which was prescribed to only one of our patients, was not efficient.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, a recent series has examined the efficacy of methotrexate in forms resistant to topical treatment. [ 11 ] In our series, the improvement under DC of localized forms is partial, which implies that acitretin seems to be efficient in diffuse forms. On the other hand, chloroquine, which was prescribed to only one of our patients, was not efficient.…”
Section: Discussionmentioning
confidence: 79%
“…However, marked improvement in extragenital lichen sclerosus with methotrexate has been shown in several studies, including in combination with pulsed high-dose corticosteroids. 9,10 To our knowledge, there are no evidence-based recommendations for systemic treatment of VLS.…”
Section: Discussionmentioning
confidence: 99%
“…3 4 Large scale studies on generalised extragenital disease are rather scarce, with case series and case reports being the source of information concerning the therapeutic approach in this case. [1][2][3][4] Kreuter et al describe a prospective study of seven patients that showed sufficient response under a regimen with pulsed intravenous high-dose corticosteroids combined with orally administered low-dose methotrexate therapy (15 mg weekly). 3 A limited number of small studies and case series describe the administration of methotrexate as monotherapy.…”
Section: Descriptionmentioning
confidence: 99%